Sosiologie en geskiedenis (Historia, 2021)
Although sociology and history started off as one discipline they gradually developed into two completely different fields of study, each with its own methods and terminology. Since the beginning of this century a growing number of historians and sociologists have argued in favour of a closer co-operation between history and sociology. In this article a plea by Van Jaarsveld for more co-operation between history and sociology, is supported and ways in which this could be done are discussed. Firstly, sociologists are cautioned not to resort to broad generalisations which are not supported by historical facts. Two abstract models which are often used by sociologists to explain social change -the linear and the cyclical model -are discussed and historians are urged to assist sociologists in gathering appropriate data to prove or disprove the validity of these models whenever they are utilised. Secondly, historians are urged to employ certain methods and techniques which were originally developed by sociologists but could also be useful to historians since they would give them access to data that would otherwise remain beyond their reach. Examples of these are: the social survey, content analysis, network analysis and the construction of ideal types. A plea is also made to historians to make more frequent use of a number of sociological concepts which may enable them to descriptionbe certain forms of human behaviour in a more precise way than was hitherto possible with purely historical concepts. Particular reference is made to the concepts ""social structure"" and ""social function"", ""social role"", ""social stratification"" and ""mentality"" and ""ideology"".
Keywords: Research methodology; Interdisciplinary studies; Sociology